Strategi Peningkatan Kualitas Pelayanan Ritel Tradisional: Studi Empati, Daya Tanggap, dan Keandalan di Toko Grosir Berkah - Muhammad Syehan; Endang Silaningsih (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to evaluate service quality and formulate service improvement strategies in traditional retail, focusing on the dimensions of empathy, responsiveness, and reliability. A descriptive qualitative method was employed through observation, interviews, and documentation at Toko Grosir Berkah, Bogor. The results indicate that although the store’s physical aspects and employees’ product knowledge are adequate, inconsistencies exist in service behavior, reactive responsiveness, and unstable product availability. Simple improvement strategies, such as encouraging employees to greet and listen to customers, establishing fast response standards, and routinely monitoring main product stocks, positively affected employee-customer interactions, service waiting times, and stock complaints. These findings highlight that enhancing service quality in traditional retail can be achieved through value internalization, simple behavioral standards, and consistent operational management. The study provides managerial implications for small-scale retail businesses and contributes to service quality theory development.